Project TILURIUM : Cross-section of Roman pottery from Tilurium. - Sanader, Mirjana; Šimić-Kanaet, Zrinka; Tončinić, Domagoj (2004)
Roman pottery from Tilurium consists of a standard pottery assemblage characteristic of the period of the Early Empire which was used in other military camps, as well as in settlements and towns in Roman provinces (Burnum, Asseria, Narona, Salona).
Dizajn postera potpisuje Danijel Šah.
Projekt MZOS
ENG